Assimilation and Changes in Cohort Quality Revisited: What Happened to Immigrant Earnings in the 1980s? - Borjas, George J. (Journal of Labor Economics, 1995)
"This article uses the 1970, 1980, and 1990 Public Use Samples of the U.S. census to document what happened to immigrant earnings in the 1980s and to determine if pre-1980 immigrant flows reached earnings parity with natives. The relative entry wage of successive immigrant cohorts declined by 9% in the 1970s and by an additional 6% in the 1980s. Although the relative wage of immigrants grows by 10% during the first 2 decades after arrival, recent immigrants will earn 15%-20% less than natives throughout much of their working lives."